Analysis of muscle activity and kinematic variables according to jump type of 3m springboard diving 109C skill -case study- - Kim, T.-W.; Kim, S.-M.; Choi, S.-H. (Korean Journal of Sport Science, 2019)
[Purpose] The purpose of this study is to overcome the shortcomings of 109C(Forward 4 ½ somersault) skill(Level 3.7) for two members of the men`s national diving team(YHR, KYN). [Methods] For qualitative analysis of the performed skill, three high-speed cameras and water-attached EMGs consisting of a total of ten placements were used. We instructed the two players to perform single-leg jump and double-leg jumps a total of three times each. [Results] The results of this study indicate that YHR and KYN appeared to increase their time or maintain the same time compared to the previous phase and displacement appeared higher when skill success occurred after the double-leg jump. The Shoulder & hip joints of YHR, KYN appeared larger in E2 and the hip joint of KYN appeared to increase in E1. Single-leg jump appeared similar or decreased the performed time of the previous phase in the last P5. YHR appeared larger only at a hip joint angle and KYN appeared smaller at the hip joint. The muscle activity(iEMG) of the two players appeared greater during skill failure than most of the muscles. [Conclusions] When perfectly performing 109C skills, the acquisition of medals in international competitions is possible. Therefore, in the future, it is necessary to study all of the variables that pertain to 109C.